2019
DOI: 10.1186/s40893-019-0039-0
|View full text |Cite
|
Sign up to set email alerts
|

GP6 rs2304166 polymorphism is associated with response to natalizumab in multiple sclerosis patients

Abstract: Background: Currently, there are few established pharmacogenetic predictors of response to treatment in multiple sclerosis (MS) patients. Commonly used second line treatments include natalizumab that has proven to be successful in slowing MS progression in a subset of patients. Our aim was to identify pharmacogenetic factor(s) associated with MS patients' response to natalizumab.Methods: Ten MS patients not responding to natalizumab and 23 MS patients responsive to natalizumab were selected for exome sequencin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Recently, a study has established to identify pharmacogenetic factor(s) associated with MS patients' response to NTZ (Tysabri), which found that the variant (rs2304166) in GP6 gene is associated with poor response to NTZ (Tysabri) in homozygous CC genotype MS patients. Al-Mojel et al (2019) investigated the possible inference of genes encoding detoxification enzyme GSTP1 and NQO1 polymorphisms on NTZ (Tysabri) response in MS, this study concluded a significantly increased frequency of double NQO1 an2d GSTP1 mutant polymorphisms in nonresponders compared to the responders (23) . In conclusion, VLA-4 polymorphisms at the level of SNP at positions 269 (C/A) have no role in MS susceptibility or NTZ responsiveness.…”
Section: A B Figure 1 Pcr Products Of Vla-4 Gen; A: a Allele In Patie...mentioning
confidence: 98%
“…Recently, a study has established to identify pharmacogenetic factor(s) associated with MS patients' response to NTZ (Tysabri), which found that the variant (rs2304166) in GP6 gene is associated with poor response to NTZ (Tysabri) in homozygous CC genotype MS patients. Al-Mojel et al (2019) investigated the possible inference of genes encoding detoxification enzyme GSTP1 and NQO1 polymorphisms on NTZ (Tysabri) response in MS, this study concluded a significantly increased frequency of double NQO1 an2d GSTP1 mutant polymorphisms in nonresponders compared to the responders (23) . In conclusion, VLA-4 polymorphisms at the level of SNP at positions 269 (C/A) have no role in MS susceptibility or NTZ responsiveness.…”
Section: A B Figure 1 Pcr Products Of Vla-4 Gen; A: a Allele In Patie...mentioning
confidence: 98%
“…The responsiveness of NAT-treated patients was determined by the presence of a steady or decreased EDSS and relapse absence. In contrast, NAT-unresponsive MS patients were diagnosed on the basis of an elevated EDSS despite treatment and the occurrence of relapses during the course of therapy [24,25]. Furthermore, the development of anti-NAT neutralizing antibodies was investigated by a specific ELISA kit to exclude antibody-positive patients from the NATunresponsive group.…”
Section: Groups Of Patients and Clinical Assessmentmentioning
confidence: 99%
“…In contrast, NAT-unresponsive MS patients were diagnosed on the basis of an elevated EDSS despite treatment alone or combined with the occurrence of relapses during the course of therapy. 28,29 The development of anti-NAT neutralizing antibodies was investigated by a specific ELISA kit to exclude antibody positive patients from the NAT unresponsive group. Four patients from group B were NAT antibody positive and they were excluded from the study.…”
Section: Patients' Groups and Clinical Assessmentmentioning
confidence: 99%